2021
DOI: 10.1093/mmy/myaa112
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of presentations and outcomes of histoplasmosis across patients with varying immune status

Abstract: Few large cohorts have examined histoplasmosis in both immunocompromised and immunocompetent patients. We describe the differences in presentations and outcomes of histoplasmosis by immune and dissemination status. We assembled a retrospective cohort of adult patients diagnosed with histoplasmosis from 2002 to 2017. Patients were grouped by immune status: people living with HIV (PLWH), patients who were HIV negative but had other-immunocompromise (OIC), and immunocompetent patients. Patients were further class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This last prevalence is in line with the 8% found in a recent systematic review of acute histoplasmosis in immunocompetent travellers [9]. One recent retrospective study of 261 cases conducted in the United States found similar prevalence of disseminated disease among PLWH (78%) and patients with OIC (58%), but a higher prevalence among immunocompetent subjects (33%) [154]. As the exposure of the majority of the immunocompetent patients considered in our review was limited to travel, it can be speculated that the higher rate of disseminated disease in the American review may have been due to greater inoculum exposure.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This last prevalence is in line with the 8% found in a recent systematic review of acute histoplasmosis in immunocompetent travellers [9]. One recent retrospective study of 261 cases conducted in the United States found similar prevalence of disseminated disease among PLWH (78%) and patients with OIC (58%), but a higher prevalence among immunocompetent subjects (33%) [154]. As the exposure of the majority of the immunocompetent patients considered in our review was limited to travel, it can be speculated that the higher rate of disseminated disease in the American review may have been due to greater inoculum exposure.…”
Section: Discussionsupporting
confidence: 81%
“…Sixty percent of the immunocompetent subjects with acute pulmonary histoplasmosis were apparently successfully treated with itraconazole. It is difficult to evaluate clinical outcomes on the basis of single case reports and small case series, but mortality rates in the different categories of patients (PLWH 24.1%; patients with OIC 32%; and immunocompetent patients 5.6%) were sufficiently similar to those reported by Franklin et al in the USA (15%; 24%, and 13%, respectively) [154].…”
Section: Discussionmentioning
confidence: 77%
“…Histoplasmosis is a common opportunistic infection in hospitalized PLWH and is associated with high mortality [ 1 , 2 , 20 , 21 ]. The risk factors for Probable/Histoplasmosis were pancytopenia, < 50 CD4 + cells/μL and high AST levels.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty diagnosing histoplasmosis can lead to delays in treatment. Failure to treat moderate-to-severe cases of histoplasmosis contributes to adverse outcomes ranging from prolonged symptoms to hospitalization and death [ 25 ]. In this paper, we estimate the incidence of diagnostic delays associated with histoplasmosis, estimate the average length of delays associated with histoplasmosis, and identify specific risk factors for diagnostic delays.…”
Section: Introductionmentioning
confidence: 99%